Perlindungan Data dan Privasi dalam Prespektif Islam - Afiqah Nur Syafitri HS; Elsa Yakub; Resky Amelia; Elisa Emi putri; Euneng Mutiara Munanda; Rabiatul Adawiyah Fair; Reski Amalia; Miftah Khaeria; Besse Ruhaya (Jurnal Sintaks Logika, 2026)
The rapid development of information technology has significantly increased personal data usage in digital activities while simultaneously creating new risks like data breaches and identity theft. These emerging challenges make personal data protection and privacy essential issues that must be examined through both positive law and Islamic values. This study specifically aims to analyze the concept of personal data protection and privacy from the perspective of Islamic law and maqashid al-shariah, examining its relevance to modern digital data governance. This qualitative research employs a comprehensive library research approach by analyzing the Qur'an, Hadith, scholarly books, and relevant legislation. The findings indicate that Islam provides a robust foundation for protecting personal data privacy through the core principles of amanah and the strict prohibition of tajassus. Furthermore, data protection closely aligns with safeguarding honor (hifz al-'ird), property (hifz al-mal), life (hifz an-nafs), and intellect (hifz al-'aql). Within Islamic criminal law, personal data misuse can be classified as jarimah ta'zir. These fundamental Islamic principles strongly align with Indonesia's Personal Data Protection Law (Law No. 27/2022), providing ethical guidance for just data governance.